Long-term forecasts of age-specific labour market participation rates with functional data models - Thomas Url; Rob J. Hyndman; Alexander Dokumentov (Austrian Institute of Economic Research (WIFO), 2016)
Many countries have implemented social programmes providing long-term financial or in-kind entitlements. These programmes often focus on specific age-groups and consequently their expenditure streams are subject to demographic change. Given the strains already existing on public budgets, longterm forecasts are an increasingly important instrument to monitor the budgetary consequences of social programmes. The expected development of the labour force is a key input to these forecasts. We suggest combining a functional data approach to age-profiles of labour market participation rates with information on education, marital status and other exogenous variables to improve long-term forecasts of labour supply.
Keywords: C14; C33; J11; 330; forecast; labour supply; age-profile; smoothing